Improvement of Microbiological Methods for Testing the Quality of Non-sterile Medicines with Antimicrobial Effects - O. V. Gunar; G. M. Bulgakova (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. Microbiological testing of any medicine begins with the determination of its antimicrobial activity—that is, its effect on the growth of aerobic bacteria, yeasts, and moulds. Therefore, the improvement of microbiological testing methods to enhance the quality of resulting data remains a high priority.AIM. The study aimed to develop a methodological approach to testing non-sterile medicines with antimicrobial effects for microbiological quality, as well as to improve the accuracy and reliability of existing microbiological testing methods.MATERIALS AND METHODS. The study used 12 non-sterile pharmaceuticals, 5 diluents (phosphate buffer solution, phosphate buffer solution with polysorbate 80 (1% and 5%), neutralising fluid, and trypticase soy broth), culture media, and test strains required for microbiological quality testing according to the State Pharmacopoeia of the Russian Federation and the Pharmacopoeia of the Eurasian Economic Union.RESULTS. This study established microbiological testing conditions for non-sterile medicines with known antimicrobial effects. The analytical procedures developed in the study were tested on 10 medicines. The authors demonstrated the applicability of analytical procedures for the quantitative determination of microscopic fungi in samples with fungistatic activity. The proliferation factors in growth promotion tests with Candida albicans and Aspergillus brasiliensis were within the acceptable range of 76–128% of the calculated value for a standardised inoculum. The authors proposed a modification to the analytical procedure for the qualitative determination of Escherichia coli; the modification involved using a 50 mL sample at a 1:50 dilution, corresponding to 1 g of the test product, for transfer to 450 mL of an appropriate culture medium. Having compared diluents containing non-specific agents neutralising antimicrobial activity, the authors showed that the neutralising fluid should be preferred.CONCLUSIONS. The authors proposed a methodological approach to microbiological quality testing of medicines, postulating that the results should be considered reliable only if they account for the antimicrobial activity of the test product. The study demonstrated the feasibility of increasing the sample volume up to 10 mL and using a dilution exhibiting no antimicrobial activity (e.g., 1:100). The authors recommended using 150 mm Petri dishes, 50 mL of an agarised culture medium, and diluents with up to 5% of polysorbate 80 for plating. The study demonstrated the suitability of using a dilution exhibiting no antimicrobial activity. The study results indicated the need to increase the sample volume to be proportionally transferred to a culture medium; the sample should contain the amount of the test product regulated by pharmacopoeias (i.e., not less than 1 g (1 mL)). Diluents with up to 5% of polysorbate 80 were recommended for neutralising bacteriostatic and fungistatic effects.